2002
DOI: 10.1007/s00421-001-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise intensity on the post-exercise esophageal temperature response

Abstract: On 2 separate days, nine volunteers aged 23.8 (2.0) years performed 15-min bouts of treadmill running in a temperature-controlled chamber at 29 degrees C at a power output that elicited either 70% (moderate) or 93% (intense) of maximum oxygen consumption. Exercise was followed by a 45-min recovery period. End-exercise esophageal temperature (Tes) was elevated by 0.97 degrees C and 2.17 degrees C above baseline for the moderate and intense exercise trials, respectively. Post-exercise Tes achieved a sustained el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 17 publications
6
36
3
Order By: Relevance
“…This finding suggests that temperature is not simply intensity dependent, which contrasts previous research (Kenny and Niedre 2002). However, the exercise intensity of 93% _ VO 2 max used in that study was much higher than that used in our current study or other research by the same group.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This finding suggests that temperature is not simply intensity dependent, which contrasts previous research (Kenny and Niedre 2002). However, the exercise intensity of 93% _ VO 2 max used in that study was much higher than that used in our current study or other research by the same group.…”
Section: Discussioncontrasting
confidence: 79%
“…These responses in skin blood flow and temperature have been reported previously by Wilkins et al (2004) who found that skin blood flow does not play and obligatory role in PEH. Furthermore, the data in this study provides support for a cardiopulmonary baroreceptor-mediated influence on postexercise skin blood flow in order to increase TPR, and suggests that post-exercise temperature regulation may be preceded by the need to regulate post-exercise blood pressure as proposed by Kenny and Niedre (2002). In summary the unique finding from this study is that the magnitude of acute PEH is clinically similar when the ''dose'' (intensity · duration) of exercise is the same for normotensive individuals.…”
Section: Discussionmentioning
confidence: 58%
“…A number of studies have shown that the duration of the postexercise hypotension in normotensive individuals may vary between 1 and 2 h after exercise (17) and that the magnitude of the response is influenced by the intensity of exercise (12). The blood pressure and HR data are consistent with a postexercise hypotensive response.…”
Section: Discussionsupporting
confidence: 66%
“…Specifically, exercise induces a residual effect on thermal control, resulting in an increase of ~0.3-0.4 °C in the postexercise esophageal temperature at which cutaneous vasodilation and sweating (Kenny et al, 2000a) occurs. Furthermore, an increase in the postexercise hypotensive response, induced by exercise of increasing intensity, was shown to result in a relative increase in the onset thresholds for cutaneous vasodilation (Kenny et al, 2003a) and ecrrine sweating (Kenny et al, 2003b), an overall decrease in the rate of heat loss, and a concomitant increase in the postexercise core temperature recovery time (Kenny and Neidre, 2002). These observations suggest a possible physiological link between the observed postexercise cardiovascular changes and the altered thermal response thresholds for cutaneous vasodilation and sweating.…”
Section: Introductionmentioning
confidence: 94%